2009
DOI: 10.1007/s11426-009-0221-x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between formate adsorption energy and electronic properties: A first principles density functional theory study

Abstract: First principles density functional theory calculations have been performed for the chemisorption of formate adsorption on some metal surfaces. For the most stable adsorption site of short-bridge, the calculated formate adsorption energy follows the order of Au(110) < Ag(110) < Cu(110) < Pd(110) < Pt(110) < Ni(110) < Rh(110) < Fe(100) < Mo(100), and a clear linear correlation exists between the adsorption energy and the corresponding heat of formation of metal oxides. Moreover, it has been found that the forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Values of the average d -band center positions (ε d ) calculated for surface atoms in contact with the adatom in Ni/Pt systems and for equivalent atoms on the clean platinum surfaces are given in Figure . It can be seen that the values obtained for the unmodified surfaces are in good agreement with previously published data, , additional evidence for the adequacy of the selected model parameters. Upon Ni adsorption, the average d -band center of platinum atoms in contact with the adatom shifts further away from the Fermi level (downshift), regardless of the surface plane.…”
Section: Resultssupporting
confidence: 87%
“…Values of the average d -band center positions (ε d ) calculated for surface atoms in contact with the adatom in Ni/Pt systems and for equivalent atoms on the clean platinum surfaces are given in Figure . It can be seen that the values obtained for the unmodified surfaces are in good agreement with previously published data, , additional evidence for the adequacy of the selected model parameters. Upon Ni adsorption, the average d -band center of platinum atoms in contact with the adatom shifts further away from the Fermi level (downshift), regardless of the surface plane.…”
Section: Resultssupporting
confidence: 87%
“…The d ‐band model is a widely accepted method to interpret interactions between adsorbates and metals 53‐56 . According to this model, the variation of adsorption energies between metal surfaces can be attributed to differences in the d ‐band structures of the various metals.…”
Section: Resultsmentioning
confidence: 99%
“…The d-band model is a widely accepted method to interpret interactions between adsorbates and metals. [53][54][55][56] According to this model, the variation of adsorption energies between metal surfaces can be This therefore suggests that the interaction between water and the adsorbate occurs nearly exclusively through the hydrogen bond (surface interactions), rather than indirectly through modification of the metal electronic states.…”
Section: Surface Electronic Effects On Observed Scalingmentioning
confidence: 99%
“…It has been reported that the formate adsorption enthalpy on the Pd, Cu and Ni follows the order of Cu (110) < Pd (110) < Ni (110) [35], which suggest that the formate adsorption enthalpy on Cu is the lowest, that is Cu can catalyze the HCOOH formation effectively. This is in accordance with our previous research, in which a HCOOH yield of 76% was obtained with the catalyst Cu [18].…”
Section: Reaction Mechanism Of the Ch 3 Cooh Formationmentioning
confidence: 99%